MORAL STATUS REVISITED: THE CHALLENGE OF REVERSED POTENCY - Baertschi, Bernard (Bioethics, 2010)
Moral status is a vexing topic. Linked for so long to the unending debates about ensoulment and the morality of abortion, it has recently resurfaced in the embryonic stem cell controversy. In this new context, it should benefit from new insights originating in recent scientific advances. We believe that the recently observed capability of somatic cells to return to a pluripotential state (a capability we propose to name ‘reversed potency’) in a controlled manner requires us to modify the traditional concept of moral status and to consider it as referring not only to intrinsic properties (like ‘to possess reason’ or ‘to be a person’), but also to extrinsic or relational ones.